A Case Study On E-Learning As A Corporate Training Tool: Employees Perspective In Tyco Healthcare - Che Din, Marlia (2007)
The aim of the study is to investigate the effectiveness of e-learning as a corporate training tool from employees's perspective. The study was carried out between two Asia countries which are Malaysia and Singapore.